Triple integrated laser – thyristor. (November 2020) - Bagaev, T.A.; Ladugin, M.A.; Padalitsa, A.A.; Marmalyuk, A.A.; Kurnyavko, Yu.V.; Lobintsov, A.V.; Danilov, A.I.; Sapozhnikov, S.M.; Krichevskii, V.V.; Konyaev, V.P.; Simakov, V.A.; Slipchenko, S.O.; et al.
Abstract: A triple laser – thyristor, i. e., a semiconductor laser with three emitting sections monolithically integrated with an electronic switch (thyristor) is experimentally studied. For comparison, the output characteristics of single and double laser – thyristors are presented. It is shown that the functional integration of a laser with a thyristor in one heterostructure allows the laser to efficiently operate in a pulsed regime (output power ∼50 W), the use of vertical integration of two laser sections increases the power to ∼90 W, and the integration of three laser sections makes it possible to increase the output optical power to ∼120 W with all other conditions being the same.